Civic Culture dalam Budaya Beguru pada Masyarakat Sasak - Igha Fattiyani Rodiatun; Lalu Sumardi; Sawaludin Sawaludin; Muh. Zubair (MANAZHIM, 2022)
The Sasak tribe has various cultures, one of which is the Beguru culture. Beguru culture is an education system based on local wisdom that practices the way of learning for the Sasak people. This study aims to determine the Beguru process, the values contained in the Beguru culture as Civic Culture and the community's efforts to maintain the existence of Beguru culture. This study uses a qualitative approach with the type of ethnographic research. Data collection techniques using interview and observation techniques. The results of this study indicate that there are five stages in the Beguru culture including: 1) The Giving Seserahan (andang-andang) stage, 2) The Ijab Kabul Stage, 3) the ascetic and bathing stage, 4) the Report and Practice Exam Stage, and the last 5) Gratitude Stage (Roah Rasul). There are three values contained in the Beguru culture as a civic culture, namely: 1) Religious Values, 2) Courtesy Values and 3) Educational Values. And there are two efforts made by the community in maintaining the existence of Beguru culture, namely: 1) Introducing Beguru culture to their children and grandchildren and 2) Implementing Beguru culture continuously.